The Decaying Rate of Organic Matter in the Inundation of PLTA Koto Panjang Reservoir, Batu Bersurat village, Sub District XIII Koto Kampar, Kampar Regency, Riau Province - Manurung, Dostiarni Minsa Karolina; Simarmata, Asmika Harnalin; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe decaying rate is the quantity of organic matter that can be decomposed by bacteria per unit time. To determine the decaying rate or the load of organic matter in the Inundation of PLTA Koto Panjang Reservoir, Batu Bersurat village, research was conducted on June-July 2019. There were three stations namely station 1(tourism area and arround of this station there were palm’s plantation), station 2 (there were restaurant and trees arround of station) and station 3 (floating cage). Each station was determined three sampling points, namely in the surface (15 cm), 2 Secchi depth (330 cm) and 4 Secchi depth (660 cm). Sampling was conducted 4 times, once/week. Water quality parameter measured were dissolved oxygen, BOD5, temperature, pH, transparancy and depth. Results shown that the value of K was 0.18/day – 0.50/day.Water quality parameter such as: dissolved oxygen was 5.42 mg/L – 7.53 mg/L, BOD5 was 4.03 mg/L – 8.90 mg/L, temperature was 28.7oC –30.7oC, pH was 5 – 5.2, transparancy was 145 cm –187.5 cm and depth was 17.7 m – 29.7 m. In the inundation of PLTA Koto Panjang reservoir in Batu Bersurat village, the decaying rate was faster than the accumulation of organic matter, except in floating cage area. Keywords : Load of organic matter, accumulation, dissolved oxygen, BOD5, water quality